IMPLEMENTASI NILAI KEADILAN SOSIAL MELALUI PENDIDIKAN PERSPEKTIF TGKH ZAINUDDIN ABDUL MAJID - Raden Samidi; Suharno Suharno (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Getting the same education is become a necessity for every citizen. The right education is part of social justice, and this becomes the ideals of Master Zainuddin Abdul Majid. The purpose of this writing is (1) to know the gait and the fight Master Zainuddin Abdul Majid in menegmbangkan education in West Nusa Tenggara, (2) to find out the values of social justice implementation of Master Zainuddin Abdul Majid in the world of education. This type of research is research studies library (library research) by examining the thinking character, approach in this study using a qualitative approach. The method of data collection in this study collects some information from several sources and primary book of scientific works of the previous studies as well as scientific journals related implementation then analyzed the value of Justice social by TGKH Zainuddin Abdul Majid through education. The results of the analysis of some of the scientific literature suggests that Master Zainuddin Abdul Majid in the biennial donations grow in West Nusa Tenggara is part of the implementation of the values of social justice, as set forth in the preamble to the Constitution 1945. Because Equalization of education is a right of every citizen are regulated by the Constitution in realizing social justice for all the people of Indonesia.